The pupils' and teachers' perceptions of e-book utilization in teaching and learning process in Setiu, Terengganu / Khairiah Abd Rahman - Abd Rahman, Khairiah (2014)
The aim of this study was to determine the pupils' and teachers' perceptions on ebook utilization for teaching and learning activities. The study was conducted in Setiu, the smallest district located in the state of Terengganu in Malaysia. Utilising a quantitative research design, the study involved Year 5 and Year 6 pupils of a total sample of 138 pupils and 60 teachers who responded to the questionnaire. The semistructured interviews were also being carried out with the pupils, the teachers and the Executive Information Officers (EIO) to triangulate the results of this study. The most interesting part of this study is that the pupils were found to use the e-book for playing computer games. It was because they were not fully exposed to the real purpose of e- Book that is to search for useful information using it. The digitalize version of primary textbook also did not exceed it fullest utilization due of the technical obstacle appeared during the implementation. The finding also revealed that a medium level of e-Book utilization among the teachers in schools. It is hoped that the teachers are given further exposure to the e-Book contents and a proper in house courses in their school can be apply so that all teachers have a better guide on the utilization. This study also suggests that parents should be expose to content of e-Book and the use of it. Short courses or briefing from schools can be done so that parents can do their part in implementing a maximize usage of e Book. It is also suggested that Executive information Officer gives maintenance courses to the pupils continously as prevention measures t o avoid further damaged e-Books. Keywords: computer, pupils, Information Communication Technology, perceive the ease of use, perceive pf usefulnes, teaching and learning,education.